Pembinaan Iman Umat di Stasi Santo Tomas Onodohalawa sebagai Wujud Kasih kepada Sesama - Martina Rosmaulina Marbun; Sergius Lay; Antonius P Sipahutar; Megawati Naibaho (Lembaga Pengembangan Kinerja Dosen, 2024)
The university community has three pillars in carrying out its duties and functions, namely the Tri Dharma of Higher Education. The three pillars are Teaching, Research, and Community Service. In this case, the service carried out is the development of faith for the people at Stasi Santo Thomas Onodohalawa. The development of the faith of the people is an act of love that aims to develop the faith of the people. The faithful of Stasi St. Thomas Onodohalawa are among the people who are willing to follow faith formation for the growth of faith that is useful for arranging a better life as Christians. The openness and enthusiasm of the people is an opportunity for STP Dian Mandala Lecturers to realize their identity as educators on campus and at the same time as solid teachers of the Catholic faith. The methods used for this community service are Liturgical Celebrations, sharing, and catechesis. This is the starting point of the need for faith development of the people at St. Thomas Onodohalawa. Based on these needs, the lecturers work together to divide the team in carrying out the coaching activities. The lecturers also involve students as a form of cadre for prospective young catechists. The preparation of the material was carried out by the team by studying together and exploring various reading sources that support the theme of community development. The purpose of this service is to help the growth of the faith of the people at the station. Thus, they are able to live in society as good and virtuous citizens in accordance with the true teachings of the Catholic faith.